IONIC LIQUID IMPREGNATED ALGINATE BEADS FOR ADSORPTION OF LEAD - SELVARAJAH, DESHALINEE (IRC, 2017)
Adsorption of lead metal ion from heavily polluted wastewaters using alginate bead immobilized with ionic liquid can be categorised as a potential biological wastewater treatment method with very less identified hazards. It is essential to separate lead ions from wastewater because lead is a toxic metal that does not undergo cyclic removal via nature sinks thus excess lead deposits stay in the environment causing further damage to environment and public health. The present study aims to study the adsorption of Pb (II) ions thus alginate (Alg) beads were synthesized using sodium alginate (Na- Alg), with ionic liquids of Bmim DCA, Bmim PF6 and Bmim NTf2 and CaCl2 as cross linker. The bead properties were analysed using SEM and FTIR. The adsorption of Pb (II) depends on type and loading of ionic liquid and initial pH of Pb (II) aqueous solution. Experimentations revealed that 25% Bmim DCA impregnated Alg bead has the highest adsorption capacity and the adsorption peaked at pH 5.5. The adsorption isotherm revealed that Pb (II) adsorption on 25% Bmim DCA-Alg is coordinated with Langmuir model. The study emphasizes the use of ionic liquid in adsorbing lead (II) ions as high adsorption capacity is registered for the 25% Bmim DCA impregnated bead when compared to the pure alginate for a period of 24 hours. The alginate beads immobilized with ionic liquid serve as biodegradable and sustainable adsorbents